Institutional hypertension control in Malaysia: a multicenter study focusing on gender and cardiovascular risk factor profile difference - Maskon, Oteh; Mohd Shah, Azarisman Shah; Syazril Adnan, Azreen; Ab Rahman, Jamalludin; Abdullah, Aszrin; Ting, Chih Kuan; Ismail, Shaiful Bahri (Nature Publishing Group, 2010)
The prevalence of hypertension in Malaysia is alarmingly high. The National Survey in 2006 showed 43% of people aged 30 had hypertension and among treated patients, only 26% reached the target blood pressure (BP) of <140/90 mm Hg. We evaluated BP control in tertiary institutions in Malaysia and the difference in hypertension control between genders and within specific cardiovascular risk factor groups. This cross-sectional study aimed at determining BP control among hypertensive patients attending three specialist institutions in Malaysia, located in Kuala Lumpur, Kuantan and Kota Bharu. A total of 950 patients with known hypertension for at least 6 months were recruited between January 2007 and July 2008. There were more males (n=548, 57.7%) with a mean age of 60.3±10.5 (±s.d.) years. The mean systolic BP (SBP) and diastolic BP were 138.8±20.3 mm Hg and 79.6±11.3 mm Hg, respectively. In total, 48.5% of all the patients had good BP control (<140/90 mm Hg). Males had better SBP control compared with female (SBP: 135.9±18.7 vs. 142.8±21.7 mm Hg, P<0.001). Overall, 54.6% of the patients had ischemic heart disease (IHD), 24.2% had undergone coronary revascularization, 50.1% were diabetic, 68.6% hyperlipidemic, 17.3% smokers and 27.5% had renal impairment. Males and small numbers of antihypertensives used were independently associated with better treatment outcome. In summary, our data reveal a poorer BP control, secondary to higher SBP levels in women. Moreover, the gender difference is more pronounced in patients with concomitant diabetes mellitus, renal impairment and IHD.